2010
DOI: 10.4238/vol9-1gmr747
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of DNA extraction from seeds and fresh leaf tissues of wild marigold (Tagetes minuta) for polymerase chain reaction analysis

Abstract: ABSTRACT. Tagetes, a genus of flowering marigolds in the family Asteraceae (Compositeae), is reported to be a medicinal plant with hypotensive, spasmolytic, anti-inflammatory, antimicrobial, and antifungal properties. Tagetes minuta characteristically contains high concentrations of essential oils, flavonoids, polyphenols, and polysaccharides that interfere with DNA, causing erroneous or no PCR products. We tested and modified various standard protocols in an effort to isolate high-quality DNA from different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…The bacterial isolates showing promising results (AZ‐1, AZ‐2, and AZ‐3) were grown in LB broth at 37 °C overnight to isolate DNA by using modified CTAB method . Part of 16S rRNA gene and mercury resistant genes ( mer A and mer B) were amplified using universal primers of 16S rRNA gene and specific primers of mer A and mer B genes in Bacillus spp.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial isolates showing promising results (AZ‐1, AZ‐2, and AZ‐3) were grown in LB broth at 37 °C overnight to isolate DNA by using modified CTAB method . Part of 16S rRNA gene and mercury resistant genes ( mer A and mer B) were amplified using universal primers of 16S rRNA gene and specific primers of mer A and mer B genes in Bacillus spp.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the current study showed low genetic diversity among the NUWYT lines resistant for stripe rust. Low level of genetic diversity was also reported among the Pakistani advanced breeding NUWYT wheat lines by Ahmed et al (2010) using the RAPD primers. This low level of genetic diversity was attributed to the existence of common parentage among these wheat lines.…”
Section: Resultsmentioning
confidence: 71%
“…DNA was extracted from fresh seedlings using Cetyl Trimethyl Ammonium Bromide (CTAB) extraction method of Shahzadi et al (2010) with some modifications. Small pieces of wheat leaves were ground to emulsion in pestle and mortar in 2 ml of CTAB…”
Section: Dna Extractionmentioning
confidence: 99%
“…The select bacterial isolates showing promising results (LPS1B, CHFT15, CHFT12, CH13, and CHP413A) were grown in LB broth at 37ºC overnight and were processed for DNA extraction using the modified CTAB method as described by Shahzadi et al [20]. Amplification of part of 16S rDNA was performed using universal primers 16S-F (5'AAACTCAAAT-GAATTGACGG3') and 16S-R (5'TCCTCCGCT-TATTGATATGC3').…”
Section: Characterization Of Bacterial Isolatesmentioning
confidence: 99%